Guided Evolution of Society - Banathy, Bela H. author. aut Link
XIX, 415 p.
Keywords: Based on a comprehensive review of human and societal evolution the book develops an approach to conscious, self-guided evolution. In the course of the evolutionary journey of our species, there have been three seminal events. The first happened some seven million yeas ago, when our humanoid ancestors entered on the evolutionary scene. Their journey toward the second crucial event lasted over six million years when - as the greatest event of our evolutionary history - homo sapiens sapiens, started the revolutionary process of cultural evolution. Today, we have arrived at the threshold of the third major event, `the revolution of conscious evolution,' when it becomes our responsibility to enter into the evolutionary design space and guide the evolutionary journey of our species. The book tells the story of the first six million years of the journey in just enough detail to understand how evolution had worked in times when it was primarily biological, driven by natural selection. With the human revolution some fifty thousand years ago, with the emergence of self-reflective consciousness, the evolutionary process transformed from biological into cultural. From this point on, the book follows the journey with detailed attention, in order to learn how cultural evolution works. The book is organized in three parts. Part One commences with an exposition of a brief history of the evolutionary idea through time with a focus on a review of the science of general evolution and specifically social and societal evolution. Next, the book unfolds the `evolutionary story' of our species from the time when the first humanoids entered the evolutionary scene to our current era. Part Two develops a systems view of evolution, explores the ways and means of how evolution works, characterizes evolutionary consciousness and develops the idea of conscious evolution. Part Three builds upon the knowledge developed in the first two parts and sets forth the key conditions of conscious, self-guided evolution, elaborating the core condition, which is the acquisition of evolutionary competence through evolutionary learning. The focus of this part is on an approach to the design of evolutionary guidance systems that our families, neighborhoods, communities, organizations, social and societal systems can use to design the future they aspire to attain. The work is set aside from other statements in three important ways. It provides: (1) a comprehensive review of how evolution has worked with a focus on socio-cultural evolution, (2) an explanation of evolutionary consciousness and the conditions of engaging in conscious evolution, and (3) most significantly, it develops a detailed approach and a methodology to the design of evolutionary guidance systems.